Pricing inertia and Frequency Response with diverse dynamics in a Mixed-Integer Second-Order Cone Programming formulation. (15th February 2020) - Badesa, L.; Teng, F.; Strbac, G.
Highlights: Marginal pricing scheme for inertia, Frequency Response and a reduced largest loss. The pricing scheme is based on an MISCOP co-optimisation of these frequency services. Our formulation can consider any combination of FR with distinct dynamics and delays. Several case studies highlight the benefits of the proposed pricing scheme. Abstract: Low levels of system inertia in power grids with significant penetration of non-synchronous Renewable Energy Sources (RES) have increased the risk of frequency instability. The provision of a certain type of ancillary services such as inertia and Frequency Response (FR) is needed at all times, to maintain system frequency within secure limits if the loss of a large power infeed were to occur. In this paper we propose a frequency-secured optimisation framework for the procurement of inertia and FR with diverse dynamics, which enables to apply a marginal-pricing scheme for these services. This pricing scheme, deduced from a Mixed-Integer Second-Order Cone Program (MISOCP) formulation that represents frequency-security constraints, allows for the first time to appropriately value multi-speed FR.